Comparative study of fiber-reinforced elastomer composites subjected to accelerated aging in water. (December 2015) - Favre, Audrey; Fotsing, Edith Roland; Levesque, Martin; Ruiz, Edu
This work focuses on the study of the hydrothermal aging of fiber-reinforced rubber composites. Physical and mechanical properties of different rubber composites as well as their influence with aging conditions were studied. Four rubber matrices were used (ethylene propylene diene monomer (EPDM), silicone, EPDM/silicone, and neoprene) to make composite samples reinforced with glass fibers. Accelerated aging in water was performed using a hot tub under controlled temperature for few months. The decrement in mechanical properties was linked to water infiltration and degradation of the fiber–matrix interface. After 6 months of accelerated aging, some samples showed an important deviation from original properties, while others retained nearly homogeneous properties with time.